Overweight and obesity as risk factors for chronic low back pain: a new follow-up in the HUNT Study - Ingrid Heuch; Ivar Heuch; Knut Hagen; John-Anker Zwart (BMC, 2024)
Abstract Background Numerous studies have examined associations between overweight and obesity and risk of low back pain (LBP), but the exact magnitude of these associations is not yet clear. The purpose of this work was to assess such sex-specific associations in a community-based setting in Norway, taking into account potential relationships with other risk factors. Methods A cohort study was conducted combining data from two waves of the Trøndelag Health Study, HUNT3 (2006-2008) and HUNT4 (2017-2019). Separate analyses were performed of risk of chronic LBP in HUNT4 among 14,775 individuals without chronic LBP in HUNT3, and of recurrence or persistence in HUNT4 among 5034 individuals with chronic LBP in HUNT3. Relative risks were estimated in generalised linear models for overweight and obesity compared to normal weight. Body size classification was based on values of BMI computed from measurements of height and weight. Chronic LBP was defined as LBP persisting at least 3 months during last year. Results After adjustment for age, smoking, physical activity in leisure time and work activity, analysis of risk among women produced relative risks 1.11 (95% CI 1.00-1.23) for overweight, 1.36 (95% CI 1.20-1.54) for obesity class I and 1.68 (95% CI 1.42-2.00) for obesity classes II-III. Relative risks among men were 1.10 (95% CI 0.94-1.28) for overweight, 1.36 (95% CI 1.13-1.63) for obesity class I and 1.02 (95% CI 0.70-1.50) for obesity classes II-III, the last estimate being based on relatively few individuals. Analyses of recurrence or persistence indicated similar relationships but with smaller magnitude of relative risks and no drop in risk among obesity classes II-III in men. The change in BMI from HUNT3 to HUNT4 hardly differed between individuals with and without chronic LBP in HUNT3. Conclusions Risk of chronic LBP increases with higher values of BMI in both sexes, although it is uncertain whether this applies to very obese men. Very obese women carry a particularly large risk. Probabilities of recurrence or persistence of chronic LBP among those already afflicted also increase with higher values of BMI. Adjustment for other factors does not influence relationships with overweight and obesity to any major extent.